Formation of ammonia–helium compounds at high pressure - Shi, Jingming (Nat Commun, 2020)
Uranus and Neptune are generally assumed to have helium only in their gaseous atmospheres. Here, we report the possibility of helium being fixed in the upper mantles of these planets in the form of NH(3)–He compounds. Structure predictions reveal two energetically stable NH(3)–He compounds with stoichiometries (NH(3))(2)He and NH(3)He at high pressures. At low temperatures, (NH(3))(2)He is ionic with NH(3) molecules partially dissociating into (NH(2))(−) and (NH(4))(+) ions. Simulations show that (NH(3))(2)He transforms into intermediate phase at 100 GPa and 1000 K with H atoms slightly vibrate around N atoms, and then to a superionic phase at  ~2000 K with H and He exhibiting liquid behavior within the fixed N sublattice. Finally, (NH(3))(2)He becomes a fluid phase at temperatures of 3000 K. The stability of (NH(3))(2)He at high pressure and temperature could contribute to update models of the interiors of Uranus and Neptune.